Ancient Ethiopian Astronomy: Cultural Foundations, Indigenous Timekeeping, and Scientific Contributions - Belay Sitotaw Goshu; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2024)
Ethiopia has a rich astronomical heritage rooted in its indigenous timekeeping systems, religious traditions, and architectural alignments. Ancient Ethiopian civilizations, including the Axumite Kingdom and the Borena Oromo, developed sophisticated methods to observe celestial bodies for agricultural, ritualistic, and governance purposes. However, these traditions remain underexplored in academic discourse. This study investigates Ethiopia’s cultural foundations in astronomy, examining the Axumite stelae alignments, the Borena calendar, and the astronomical significance of Lalibela’s rock-hewn churches. It also compares Ethiopian astronomical knowledge with Egyptian, Mesopotamian, and Greco-Roman systems to evaluate its uniqueness and scientific contributions. Archaeo-astronomical analysis, ethnographic interviews, and observational research were all used in a mixed-methods approach. Stellarium and NASA's SkyView software were employed to examine the Axumite and Lalibela structures, verifying their celestial alignments. In addition to literary surveys of historical books and religious manuscripts, interviews with elders, religious experts, and Borena timekeepers were conducted to study traditional timekeeping. Findings confirm that Axumite monuments exhibit solstitial and equinoctial orientations, suggesting astronomical intent. The Borena calendar was validated as a precise lunar-stellar system, demonstrating advanced celestial knowledge. Lalibela’s churches show possible astronomical alignments, reinforcing the integration of astronomy into Ethiopian religious practices. Comparisons with other ancient civilizations highlight Ethiopia’s distinctive yet interconnected astronomical legacy. Conclusion: Ethiopia’s astronomical heritage is scientifically significant yet underdocumented. The decline in traditional knowledge transmission threatens its preservation. The preservation of indigenous astronomical practices, their incorporation into the curriculum, and the encouragement of cultural tourism should be the top priorities of future study to safeguard Ethiopia's contributions to international astronomy.